Changes in cross-bridge cycling underlie muscle weakness in patients with tropomyosin 3-based myopathy - Ottenheijm, C. A. C.; Lawlor, M. W.; Stienen, G. J. M.; Granzier, H.; Beggs, A. H. (Human molecular genetics, 2011)
Nemaline myopathy, the most common non-dystrophic congenital myopathy, is caused by mutations in six genes, all of which encode thin-filament proteins, including NEB (nebulin) and TPM3 (α tropomyosin). In contrast to the mechanisms underlying weakness in NEB-based myopathy, which are related to loss of thin-filament functions normally exerted by nebulin, the pathogenesis of muscle weakness in patients with TPM3 mutations remains largely unknown. Here, we tested the hypothesis that the contractile phenotype of TPM3-based myopathy is different from that of NEB-based myopathy and that this phenotype is a direct consequence of the loss of the specific functions normally exerted by tropomyosin. To test this hypothesis, we used a multidisciplinary approach, including muscle fiber mechanics and confocal and electron microscopy to characterize the structural and functional phenotype of muscle fibers from five patients with TPM3-based myopathy and compared this with that of unaffected control subjects. Our findings demonstrate that patients with TPM3-based myopathy display a contractile phenotype that is very distinct from that of patients with NEB-based myopathy. Whereas both show severe myofilament-based muscle weakness, the contractile dysfunction in TPM3-based myopathy is largely explained by changes in cross-bridge cycling kinetics, but not by the dysregulation of sarcomeric thin-filament length that plays a prominent role in NEB-based myopathy. Interestingly, the loss of force-generating capacity in TPM3-based myopathy appears to be compensated by enhanced thin-filament activation. These findings provide a scientific basis for differential therapeutics aimed at restoring contractile performance in patients with TPM3-based versus NEB-based myopathy.